2016
DOI: 10.5194/acp-16-1491-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineral dust on global atmospheric nitrate concentrations

Abstract: Abstract. This study assesses the chemical composition and global aerosol load of the major inorganic aerosol components, focusing on mineral dust and aerosol nitrate. The mineral dust aerosol components (i.e., Ca 2+ , Mg 2+ , K + , Na + ) and their emissions are included in the ECHAM5/MESSy Atmospheric Chemistry model (EMAC). Gas/aerosol partitioning is simulated using the ISORROPIA-II thermodynamic equilibrium model that considers K + , Ca 2+ , Mg 2+ , NH Emissions of mineral dust are calculated online by ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 99 publications
2
108
0
Order By: Relevance
“…The interface structure of MESSy links the base model with several atmospheric submodels that online simulate gas-phase chemistry (MECCA; Sander et al, 2011), inorganic aerosol microphysics and dynamics (GMXe; Pringle et al, 2010), organic aerosol formation and growth (ORACLE; Tsimpidi et al, 2014), emissions (ONLEM and OFFLEM; Kerkweg et al, 2006b), dry deposition and sedimentation (DRYDEP and SEDI; Kerkweg et al, 2006a), cloud scavenging (SCAV; Tost et al, 2006), cloud microphysics (CLOUD; Bacer et al, 2018), and aerosol optical properties (AEROPT; Lauer et al, 2007). EMAC has been extensively described and evaluated against ground-based and satellite observations (Pozzer et al, 2012;Tsimpidi et al, 2014Tsimpidi et al, , 2016Tsimpidi et al, , 2017Karydis et al, 2016Karydis et al, , 2017. In this study, the applied spectral resolution of the EMAC model is T63L31, corresponding to a horizontal grid resolution of 1.875 • × 1.875 • and 31 vertical layers extending to 18 km of altitude (10 hPa).…”
Section: Emac Modelmentioning
confidence: 99%
“…The interface structure of MESSy links the base model with several atmospheric submodels that online simulate gas-phase chemistry (MECCA; Sander et al, 2011), inorganic aerosol microphysics and dynamics (GMXe; Pringle et al, 2010), organic aerosol formation and growth (ORACLE; Tsimpidi et al, 2014), emissions (ONLEM and OFFLEM; Kerkweg et al, 2006b), dry deposition and sedimentation (DRYDEP and SEDI; Kerkweg et al, 2006a), cloud scavenging (SCAV; Tost et al, 2006), cloud microphysics (CLOUD; Bacer et al, 2018), and aerosol optical properties (AEROPT; Lauer et al, 2007). EMAC has been extensively described and evaluated against ground-based and satellite observations (Pozzer et al, 2012;Tsimpidi et al, 2014Tsimpidi et al, , 2016Tsimpidi et al, , 2017Karydis et al, 2016Karydis et al, , 2017. In this study, the applied spectral resolution of the EMAC model is T63L31, corresponding to a horizontal grid resolution of 1.875 • × 1.875 • and 31 vertical layers extending to 18 km of altitude (10 hPa).…”
Section: Emac Modelmentioning
confidence: 99%
“…For this purpose, we have generated maps of the desert soil composition (Fig. 6) based on the fractions reported by Karydis et al (2016) and geographical data from the Natural Earth data set (Natural Earth, 2016). The chemical composition does not affect the amount of dust emitted, but the chemical ageing of airborne dust particles simulated by the GMXe submodel can affect the atmospheric residence time (Abdelkader et al, 2015) and the optical properties (Klingmüller et al, 2014).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Anthropogenic NO − 3 and SO 2− 4 mainly contribute to the chemical aging of dust over continents, while sea-salt-derived Cl − is more important over oceans (Sullivan et al, 2007;Fountoukis et al, 2009;Dall'Osto et al, 2010;Tobo et al, 2010;Karydis et al, 2011b;Bougiatioti et al, 2016b;Weber et al, 2016). Apart from the gas-phase composition, the chemical processing of dust also depends on its chemical composition and thus on the source region (Sullivan et al, 2009;Karydis et al, 2016). Several studies have revealed that Saharan dust can be efficiently transported over the Mediterranean Basin, where it can acquire significant soluble coatings (mostly sea salt and sulfate) resulting in the enhancement of its hygroscopicity and CCN activity (Wurzler et al, 2000;Falkovich et al, 2001;Smoydzin et al, 2012;Abdelkader et al, 2015).…”
mentioning
confidence: 99%
“…Few global studies have accounted for the thermodynamic interactions of crustal elements with inorganic aerosol components (Feng and Penner, 2007;Fairlie et al, 2010;Xu and Penner, 2012;Hauglustaine et al, 2014;Karydis et al, 2016). Most of these models either neglect the impact of dust on cloud droplet formation or apply simplified assumptions about the CCN activity of dust, e.g., they convert "hydrophobic" dust to "hydrophilic" dust by applying a constant κ-hygroscopicity (e.g., 0.1) and use Köhler theory to describe cloud droplet activation.…”
mentioning
confidence: 99%